Chemotherapy-Induced Changes in Plasma Amino Acids and Lipid Oxidation of Resected Patients with Colorectal Cancer: A Background for Future Studies - Aquilani, Roberto; Brugnatelli, Silvia; Maestri, Roberto; Iadarola, Paolo; Corallo, Salvatore; Pagani, Anna; Serra, Francesco; Bellini, Anna; Buonocore, Daniela; Dossena, Maurizia; Boschi, Federica; Verri, Manuela (International journal of molecular sciences, 2024)
Previous studies have documented that FOLFOX and XELOX therapies negatively impact the metabolism of skeletal muscle and extra-muscle districts. This pilot study tested whether three-month FOLFOX or XELOX therapy produced changes in plasma amino acid levels (PAAL) (an estimation of whole-body amino acid metabolism) and in plasma levels of malondialdehyde (MDA), a marker of lipid hyper oxidation. Fourteen ambulatory, resected patients with colorectal cancer scheduled to receive FOLFOX (n = 9) or XELOX (n = 5) therapy, after overnight fasting, underwent peripheral venous blood sampling, to determine PAAL and MDA before, during, and at the end of three-month therapy. Fifteen healthy matched subjects (controls) only underwent measures of PAAL at baseline. The results showed changes in 87.5% of plasma essential amino acids (EAAs) and 38.4% of non-EAAs in patients treated with FOLFOX or XELOX. These changes in EAAs occurred in two opposite directions: EAAs decreased with FOLFOX and increased or did not decrease with XELOX (interactions: from p = 0.034 to p = 0.003). Baseline plasma MDA levels in both FOLFOX and XELOX patients were above the normal range of values, and increased, albeit not significantly, during therapy. In conclusion, three-month FOLFOX or XELOX therapy affected plasma EAAs differently but not the baseline MDA levels, which were already high.